2014
DOI: 10.1530/jme-14-0089
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD163 mRNA and soluble CD163 protein in human adipose tissue in vitro

Abstract: CD163-positive macrophages are highly expressed in the human adipose tissue (AT) particularly from obese individuals. However, little is known about the regulation of CD163 mRNA and the protein level of sCD163 in human AT. We aimed to examine the regulation of CD163 and sCD163 in AT. Human s.c. AT samples (nZ5) were stimulated with dexamethasone (DEX; 200 nmol/l), lipopolysaccharide (LPS; 100 ng/ml), or DEXCLPS for various time periods up to 24 h. Gene expressions of CD163, ADAM17, IL10, and TNFA (TNF) were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Microbial translocation may also play a role in the association seen between sCD163 and insulin resistance. Markers of microbial translocation have been associated with insulin resistance [ 37 ] and are known to stimulate the release of sCD163 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial translocation may also play a role in the association seen between sCD163 and insulin resistance. Markers of microbial translocation have been associated with insulin resistance [ 37 ] and are known to stimulate the release of sCD163 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with a number of studies that have identified associations between sCD163 and cardiovascular inflammation and atherosclerotic plaque formation in the setting of HIV infection [ 14 , 23 25 ] as well as in the general population [ 23 , 26 , 27 ]. This association appears to be underpinned by the role of activated monocyte-derived macrophages within atherosclerotic vessels [ 28 ] as well as in adipose tissue [ 29 , 30 ] in producing sCD163. This pathway involves tumor necrosis factor-alpha (TNF-α) and ADAM-17 [ 30 , 31 ], thus providing a link between inflammation and atherosclerotic risk factors including oxidised lipids that may be particularly relevant in HIV infection [ 32 , 33 ] but are rarely measured in routine care.…”
Section: Discussionmentioning
confidence: 99%
“…This association appears to be underpinned by the role of activated monocyte-derived macrophages within atherosclerotic vessels [ 28 ] as well as in adipose tissue [ 29 , 30 ] in producing sCD163. This pathway involves tumor necrosis factor-alpha (TNF-α) and ADAM-17 [ 30 , 31 ], thus providing a link between inflammation and atherosclerotic risk factors including oxidised lipids that may be particularly relevant in HIV infection [ 32 , 33 ] but are rarely measured in routine care.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that elevated circulating IL-6 levels are associated with worsened lung function [18], increased exacerbations of airway disease [33], and neutrophilic asthma [34]. In adipose tissue, CD163 gene expression reflects the level of anti-inflammatory (M2) macrophage infiltration [35]. Our finding of increased CD163 gene expression in adipose tissue from Greenland dwelling Inuit is consistent with a less inflammatory state, which is corroborated by finding less IL-6 and IL-1b in Greenland dwelling Inuit adipose tissue biopsies.…”
Section: Discussionmentioning
confidence: 99%